Organism–Materials Integration: A Promising Strategy for Biomedical Applications. Issue 2 (18th December 2020) - Cui, Yihao; Li, Benke; Wang, Xiaoyu; Tang, Ruikang
Abstract : In nature, organisms play an essential role in harnessing elements to produce materials. Being precisely integrated with the biological structures, the materials confer organisms with various unique functions such as protection, recognition guiding, biocatalysis, etc. Inspired by this phenomenon, elaborately designed materials can be grafted to different organisms such as cells, eukaryotes, and viruses via artificial incorporation strategies. Herein, progresses upon the methods and techniques of organism–materials integration are discussed, including spontaneous formation, artificial enhancement, and genetic engineering. The integration of organism and materials can alter the biological behavior and even offer the organism rationally designed functions, facilitating the biological applications of organisms in the field such as vaccine improvement, biomedical therapy, and biomedical imaging. These unique effects achieved by the combination of organisms and materials propose a new strategy for providing precise control over organisms. These promising strategies also offer new perspectives of biology and chemistry development, and show great potential in future biomedical therapy. Abstract : Herein, a summary upon organisms integrated with materials is given. Common materials and basic methods to fabricate an organism–materials hybrid are introduced and recent strategies are described in detail. Finally, applications of organism–materials integrant in biomedical field are represented. It is believed this work demonstrates organism–materials integration as a promising strategy in future applications.